The Effectiveness of Health Education Using Video Media on Tooth Brushing Skills of Preschool Children at Nur Handayani Kindergarten, Telaga Biru District - Sindy Oktaviani H. Dg Sewang; Andi Akifa Sudirman; Dewi Modjo (Universitas Muhammadiyah Palu, 2025)
Dental and oral health issues, particularly dental caries, remain a significant health problem in preschool-aged children. Poor independent and correct tooth-brushing skills increase the risk of tooth decay. One effective way to improve tooth-brushing skills is through health education using interactive video media. This study aimed to determine the effect of health education using video media on improving tooth-brushing skills in preschool-aged children at Nur Handayani Kindergarten, Telaga Biru District. The study design used a quantitative approach with a pre-experimental one-group pretest-posttest method. The subjects were 41 children aged 5-6 years. Health education was provided through interactive video media for 30-60 minutes. Data collection was conducted through observations before and after the intervention. Data analysis used the non-parametric Wilcoxon statistical test due to the non-normal distribution of the data. Before the intervention, the majority of respondents (78%) had poor tooth-brushing skills. After the provision of health education using video media, there was a significant increase, with the proportion of good categories reaching 46.3% and sufficient categories reaching 48.8%. The Wilcoxon test showed a p-value of 0.000 (<0.05), proving that the intervention had a statistically significant effect on improving tooth-brushing skills. Health education using video media effectively improved tooth-brushing skills in preschool-aged children. Interactive video media captured children's attention and facilitated their understanding of proper tooth-brushing techniques.